APAKAH MOTIVASI MEMEDIASI HUBUNGAN ANTARA REMUNERASI DAN KINERJA DOSEN? - Toni nurhadianto; ulfah tika Saputri; fitri Agustina (Universitas Teknokrat Indonesia, 2023)
AbstractThis study aims to examine the remuneration and motivation that affect the performance of lecturers. Remuneration is an independent variable, motivation is an intervening variable and lecturer performance is a dependent variable. The data were analyzed using the Structural Equation Model (SEM) with Smart PLS software. The sampling method used is the purposive sampling method. The data used are primary data, which is in the form of respondents' perceptions of variables using questionnaires. To prove the hypothesis is done by testing validity and reliability. The results showed that Remuneration had a positive effect on lecturer performance, remuneration had a positive effect on lecturer motivation while motivation as a mediating variable had no effect on lecturer performance. Keywords: Remuneration, Motivation, and Lecturer Performance